Detection of cross infections by Leishmania spp. and Trypanosoma spp. in dogs using indirect immunoenzyme assay, indirect fluorescent antibody test and polymerase chain reaction - Viol, M. A. [UNESP]; Lima, V. M. F. [UNESP]; Aquino, M. C. C. [UNESP]; Gallo, G. [UNESP]; Alves, I. P. [UNESP]; Generoso, D. [UNESP]; Perri, S. H. V. [UNESP]; Lucheis, Simone Baldini [UNESP]; Langoni, Hélio [UNESP]; Nunes, C. M. [UNESP]; Bresciani, Katia Denise Saraiva [UNESP] (Springer, 2012)
The aim of this study was to detect cross infections by Leishmania spp. and Trypanosoma spp. using enzyme-linked immunosorbent assay (ELISA), indirect fluorescent antibody test (IFAT) and polymerase chain reaction (PCR). Thus, 408 blood samples were collected from dogs domiciled in Ara double dagger atuba Municipality, So Paulo State, Brazil; the dogs were of both sexes, of several breeds and aged 6 months. For Leishmania spp., 14.95 % (61 out of 408) of dogs were reactive using IFAT. Positivity was 20.10 % (82 out of 408) using ELISA and 29.66 % (121 out of 408) using PCR, with significant differences for the sex and age of these animals (p < 0.05). For Trypanosoma spp., antibody occurrence using ELISA was 10.54 % (43 out of 408), while PCR indicated 2.45 % (10 out of 408) positive dogs. Using IFAT, 10.29 % (42 out of 408) of animals were considered positive and only sex showed a significant difference (p < 0.05). In this study, 10.54 % (43 out of 408) of animals were seropositive according to ELISA for Trypanosoma spp., of which 79.07 % (34 out of 43) showed positive results in the molecular diagnosis for Leishmania spp., while of the 10.29 % (42 out of 408) positive dogs according to IFAT, 95.24 % (40 out of 42) had confirmed infection by this parasite. The obtained results demonstrate evidence of cross infections by both protozoa in the animals analysed in this study.